A comparative study of ultrasound-guided puncture biopsy combined with histopathology and Xpert MTB/RIF in the diagnosis of lymph node tuberculosis - Meng, Xiangyu; Fu, Hongxiang; Jia, Weina; Wang, Ying; Yang, Gaoyi (Frontiers in Public Health, 2023)
Background: Cervical tuberculous lymphadenitis (CTBL) is a disease often ignored in clinical work, and pathology and Xpert MTB/RIF(Xpert) are the commonly used methods for tuberculosis diagnosis.This study aimed to compare ultrasound-guided puncture biopsy combined with histopathology and Xpert in the diagnosis of lymph node tuberculosis. METHODS: A total of 217 patients highly suspected for CTBL disease were retrospectively enrolled. All patients were puncture sampling by ultrasound-guided . All samples were examined by pathological examination and Xpert test. The ensitivity and specificity of the two methods were compared.Using comprehensive diagnosis as the gold standard, the kappa value was calculated to evaluate the consistency of pathological examination and Xpert test. Receiver operating characteristic curves of the pathological examination, Xpert test, and their combination were generated, and the areas under the curve (AUCs) were calculated to compare the diagnostic value of the three methods. RESULTS: The sensitivity and specificity of the pathological diagnosis of CTBL were 70.1% and 100%, respectively. The sensitivity and specificity of Xpert for CTBL diagnosis were 82.5% and 97.5%, respectively.The results of pathological examination and Xpert test showed poor consistency in the diagnosis of CTBL, with a kappa value of 0.388. The AUC of the pathological diagnosis of CTBL was 0.850 (95%CI: 0.796–0.895). The AUC of Xpert for the diagnosis of CTBL was 0.900 (95%CI: 0.852–0.936), and the difference was statistically significant (P = 0.0483). The AUC of pathological examination combined with Xpert in the diagnosis of CTBL was 0.956 (95%CI was 0.920–0.979), and the difference between pathological examination combined with Xpert in the diagnosis of CTBL was statistically significant compared with pathological examination alone and Xpert alone, respectively (both P < 0.001). CONCLUSIONS: The diagnostic efficiency of Xpert test is higher than that of pathological examination, but its sensitivity is still not ideal for clinical diagnosis. According to this study, the consistency of Xpert test and pathological diagnosis is poor, and the combination of Xpert test and pathological diagnosis can significantly increase the diagnostic efficiency.